The SISTEM REKOMENDASI PEMILIHAN PAKET PEMBUATAN WEBSITE MENGGUNAKAN METODE KNOWLEDGE-BASED RECOMMENDATION PADA PT. TEBAR DIGITAL KREASI - Pratama, Dika Adi; Nurmalitasari; Irawan, Ridwan Dwi (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
A website is a necessity for individuals, groups, and large companies in the current era of internet development. PT. Tebar Digital Kreasi, a company providing website creation and development services in the Solo area, faces challenges in helping clients choose the right website creation package that suits their needs. Without a recommendation system, the package selection process requires direct communication with the marketing team, which can be inefficient and time-consuming. The aim of this research is to design and develop a recommendation system by applying the Knowledge-Based Recommendation method. The method for developing this system is Agile Software Development. The development stages include needs analysis, Unified Modeling Language (UML) system design, and database implementation. System testing was conducted using the Blackbox method, and performance was measured using recall and precision metrics. The test results indicate that the developed recommendation system successfully provides accurate and relevant recommendations according to user needs. The recall value reached 100%, demonstrating the system's ability to retrieve all relevant data items, while the precision value reached 89.43%, indicating the accuracy of the relevant items displayed.